The determinants of service export in Malaysia / Nur Hanisah Jamil - Jamil, Nur Hanisah (2017)
The insufficient knowledge on what the performance of services export in Malaysia is becoming more concern. Besides product and goods, a lot of strategies and improvement need to undertake in order to drive export growth of service in Malaysia. Recently the lag between imported services is bigger than exported services. The problem of deficit in services export cannot be simply solved by spending more money on development but also need to improve the management. There is an urgent need for innovation, for better understanding on how to achieve the target to increase revenue for exported services rather than imported services. This research aims to study the relationship of commercial service export with four determinants, namely foreign direct investment (FDI), gross domestic product (GDP), export of merchandise goods and value-added service. It specifically studies on services trade in Malaysia. Sample years are 1975 to 2014. Ordinary least square (OLS) is used. Results revealed that foreign direct investment, gross domestic product and export of merchandise goods has positive relationship with commercial service export. However, value added service shows a negative relationship with commercial service export.